Bioethical challenges of the DSM-5. Rupture, recalibration, or more of the same? - Figueroa, Gustavo (Acta Bioethica, 2021)
1] The DSM-5 represents the incorporation of psychiatry into evidence-based medicine. 2] The psychiatry proper to the intention was transformed into that based on empirical validation. 3] The DSM-5 is an expression of modern science that gives priority to calculating, objectifying, classifying, operational knowledge. 4] An ethic of autonomy and fairness characteristic of verification was superimposed on the ethics of beneficence proper to the intention. 5] DSM-5 cannot determine whether psychiatric disorders are natural entities, practical types made by researchers, socially constructed entities, labels that are grouped into a system.